Soil carbon and microbes in the warming tropics. (15th May 2022) - Nottingham, Andrew T.; Gloor, Emanuel; Bååth, Erland; Meir, Patrick
Abstract: Climate warming could destabilise the Earth's largest terrestrial store of reactive carbon (C), by accelerating the decomposition of soil organic matter. A third of that C store resides in the tropics. The potential for tropical soils to sequester C, or to act as an additional source of CO2, will depend on the balance of C inputs and outputs, mediated by the response of soil microbial communities and their activity to perturbation. We review the impact of warming on microbial communities and C storage in humid tropical forest soils over multiple time‐scales. Recent in situ experiments indicate high sensitivity of tropical forest soil C mineralisation to warming in the short term. However, whether this will translate into long‐term soil C decline remains unclear. At decadal time‐scales, high sensitivity of soil C mineralisation to warming is consistent with the correlation between the inter‐annual variation in the tropical land surface temperature and atmospheric CO2 growth rate, and with simulations using the Carnegie‐Ames‐Stanford Approach biosphere model. This observed sensitivity may further contribute to climatic change over millennial time‐scales, suggested by radiocarbon dating of organic matter in river basins showing a twofold acceleration in tropical soil C release during the late‐glacial warming period. However, counter to this evidence, long‐term stability of tropical soil C is suggested by observed steady‐state soil C turnover across temperature gradients with elevation, and by the presence of C in tropical soils that pre‐dates the Holocene Thermal Maximum and late‐glacial warming periods. To help reconcile these recent experimental findings and long‐term observations, we propose mechanisms to explain tropical soil C and microbial responses to warming across multiple time‐scales. Combined in situ experimental and monitoring approaches—large‐scale and cross‐site—are urgently needed to resolve the interplay of these mechanisms across spatial and temporal scales, to shape a better understanding of the relationship between soil microbes and C storage in tropical soils. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.